ANALYSIS STUDENTS’ PROBLEMS IN LEARNING LISTENING COMPREHENSION SKILLS - Sawal, An-nafi; Jamiluddin, Jamiluddin; Mashuri, Mashuri; Aminah, Aminah (Tadulako University, 2025)
This research is aimed to identify students’ problems of listening comprehension skill. The researcher took the third semester students as the respondents in this research. The research design used in this research is descriptive qualitative research. 15 students out of 294 students were selected as the respondents. They were given questionnaire to collect the data for this qualitative research. Questionnaire result was analyzed based on thematic analysis procedures. Questionnaire was done by given twenty assessment prepared. Based on the result of this research, the students had three major problems in learning listening comprehension, first length and speed and variety accent, second lack of vocabulary and the last is lack of concentration. From the results of these findings, the researcher suggests two strategies. First for the students, the students are expected to be able to practice and get used to hearing various accents and different speed variations. Regular vocabulary practice looking for relevant learning resources can improve students’ vocabulary and the last is prioritizing listening, active involvement, and applying concentration techniques can help students overcome concentration disorders and improve students’ listening comprehension. Second, for the lecturer by knowing students’ problems learning listening comprehension, the lecturer can effectively support students in improving their listening skills and achieve better results for students to learning listening comprehension skills.